(untitled) (Eurasian Medical Research Periodical, 2024)
Renal development anomalies are intrauterine disorders of kidney formation caused by genetic mutations and the impact of teratogenic factors on the foetus in the first trimester of pregnancy. They are manifested by pain in the lumbar region, attacks of renal colic, fever, general weakness, changes in urine and blood. Diagnosed by ultrasound with Doppler, excretory urography, CT, MRI, laboratory tests and other methods. Treatment of renal anomalies includes uroseptic, antibiotics, hypotensive drugs. If indicated, extra kidney removal, cyst removal and other surgeries are performed.